Pengembangan Media Pembelajaran Audio Visual Berbantuan Aplikasi Geogebra Classic 5 3D Pada Materi Bangun Ruang Oleh Siswa Kelas V SDN 105380 Kramat Gajah Tahun Ajaran 2024 - Jimi Pratama; Nuri Ramadhan; Astria Ayu Ramadianti (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2025)
This project involves the development of audiovisual learning media using the Geogebra Classic program, which specifically focuses on building materials for Class V at SDN 105380. This study is based on the inadequate use of technology by educators, especially in the application of learning media for teaching mathematics. To improve the teaching of mathematics using building materials, audiovisual learning media using the Geogebra Classic 5 program was created to diversify math learning resources and increase student engagement in math classes. This study uses ADDIE paradigm. This Model represents analysis, design, development, implementation, and evaluation. This study involved a cohort of 32 students from Class V SDN 105380. This research instrument uses questionnaires that include validation questionnaires for two experts, instructor effectiveness questionnaires, and student effectiveness questionnaires. The findings of this study indicate the creation of appropriate resources for the learning process, achieving an average value of 80% in the very feasible category according to the material validator, and a value of 88% in the very feasible category according to the media validator. The efficacy of Learning media resulted in scores of 93% for teacher responses and 87% for student responses, indicating that the criteria for Learning media are very successful. Based on these results, it can be concluded that the audio-visual learning media assisted by the geogebra application has been declared very feasible and effective.